A metasynthesis study of family caregivers' transition experiences caring for community-dwelling persons with advanced cancer at the end of life. (July 2017) - Duggleby, Wendy; Tycholiz, Jamie; Holtslander, Lorraine; Hudson, Peter; Nekolaichuk, Cheryl; Mirhosseini, Mehrnoush; Parmar, Jasneet; Chambers, Thane; Alook, Angele; Swindle, Jennifer
Background: Family caregivers (broadly defined as family and friends) experience multiple concurrent transitions when caring for a person with advanced cancer. Aims: To (a) explore the transition experience of family caregivers caring for persons with advanced cancer living in the community, (b) describe potential triggers for transitions, (c) identify what influences this experience, and (d) develop a conceptual framework of their transition experience. Design: Sandelowski and Barroso's methodology for synthesizing qualitative research included (a) a comprehensive search of empirical literature, (b) quality appraisal of qualitative studies, (c) classification of studies, and (d) synthesis of the findings. Data sources: Literature was sourced from six electronic data bases. Inclusion criteria were as follows: (a) published qualitative studies (and mixed-method designs) of the caregiving experience of family caregivers of community-living persons with advanced cancer at the end of life, (b) participants (caregivers and care recipients) of 18 years of age and above, (c) studies published in English in any country, and (d) studies published between 2004 and 2014. Results: A total of 72 studies were included in the metasynthesis. Family caregivers experience a "life transition" whereby their lives are permanently altered. The participants described the process of redefining normal which consisted of coming to terms with their situation and connecting with others. Outcomes of these processes were as follows: (a) maintaining a sense of personhood, (b) reframing hope, (c) maintaining self-efficacy, (d) finding meaning, and (e) preparing for the death of their care recipient. Conclusion: The findings provide a framework to guide the development of supportive programs and future research.